A Novel Student-Initiated International Emergency Medicine Competition: A Decade of Experience from the Khon Kaen University International Challenge of Emergency Medicine - Yui Okamura; Parames Ngeabngamsri; Ami Iwano; Thanachit Krikeerati; Kotaro Yanagisawa; Thanut Jansirirat; Moeko Ohkoshi; Tomonari Shimoda; Thomas Mayers; Praew Kotruchin; Pattarapong Makarawate (Emergency Care and Medicine)
The global health crisis caused by the COVID-19 pandemic severely restricted in-person international events and clinical exposure opportunities for medical students. As a result, fostering global collaborations and providing hands-on experiences for future healthcare professionals has become increasingly challenging. The Khon Kaen University International Challenge of Emergency Medicine (KKU ICEM) is the world’s first international emergency medicine (EM)-focused competition for medical students. Since 2016, it has been held eight times and attracted participation from approximately 500 students across 18 countries spanning Asia, Europe, North America, and Africa. The KKU ICEM not only equips medical students with essential EM knowledge but also cultivates international friendships and cross-cultural competence. Initiatives like the KKU ICEM can play a crucial role in preparing the next generation of healthcare professionals for the challenges ahead.